2012
DOI: 10.4172/2155-6113.1000175
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Histoplasmosis Seasonal Incidence Variations: A Supplementary Argument for Recent Infection?

Abstract: International audienceBackground: In French Guiana, a recent study has shown that a major part of the histoplasmosis incidence temporal fluctuations could be explained by climatic factors and thus postulated that disseminated histoplasmosis cases could be in a large proportion due to new infections. The description of the seasonal pattern of histoplasmosis could potentially help to test this new hypothesis. Patients and methods: A study using prospective data from the French Hospital Database for HIV was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…32 The ideal conditions for the development of Histoplasma capsulatum and its subsequent dispersion in the environment can be favoured by climatic variables, and the higher incidence of histoplasmosis in HIV patients can be significantly associated to seasonal cycles. 33 Our data support several studies that affirm the strong influence of rain on the incidence of mycoses. 6,7,14,30,31,34,35 Climatic variables, such as precipitation and temperature, are known to affect the incidence of coccidioidomycosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…32 The ideal conditions for the development of Histoplasma capsulatum and its subsequent dispersion in the environment can be favoured by climatic variables, and the higher incidence of histoplasmosis in HIV patients can be significantly associated to seasonal cycles. 33 Our data support several studies that affirm the strong influence of rain on the incidence of mycoses. 6,7,14,30,31,34,35 Climatic variables, such as precipitation and temperature, are known to affect the incidence of coccidioidomycosis.…”
Section: Discussionsupporting
confidence: 90%
“…The decreasing maximum temperature is an environmental factor that can be associated to a high‐risk to hospitalisation owing to blastomycosis . The ideal conditions for the development of Histoplasma capsulatum and its subsequent dispersion in the environment can be favoured by climatic variables, and the higher incidence of histoplasmosis in HIV patients can be significantly associated to seasonal cycles …”
Section: Discussionmentioning
confidence: 99%
“…Further, his residence was close to Ganges belt from where cases of Histoplasma have been reported frequently [ 6 ]. There are not many studies to prove seasonal variation, but one French study showed a peak of infection during a long dry season [ 9 ]. Similar to our case that has been symptomatic in July 2014, there was another case presented in July 2012 as reported from Southern India [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of HIV-infected persons living in endemic French Guiana, where the prevalence of positive skin tests is around 30%, we found that the incidence rate of disseminated histoplasmosis increased sharply as CD4 counts dropped below 100 per μL exceeding 10 per 100 person years, with a significant seasonal effect and a risk difference of 0.7 per 100 person years between dry and wet seasons [ 7 , 8 ]; the attributable risk percent in the overall HIV cohort (61%) implies that, overall, 61% of cases were attributable to the dry season and, arguably, to newly acquired infections. Hence, for patients in our HIV cohort, and presumably most cohorts in endemic Latin America [ 9 ], there is regular exposure to a major pathogen for most patients and thus possibility of prevention of infection and dissemination.…”
Section: Evidence For De Novo Infections and Asymptomatic/paucisympto...mentioning
confidence: 99%